2017
DOI: 10.1108/ils-03-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Essential teaching methods to enhance learner academic achievement in physical sciences in rural secondary schools

Abstract: Purpose The purpose of this paper is to explore teaching methods that can allow learners to be creative and proactive. The learners should be able to solve problems, make decisions, think critically, communicate ideas effectively and work efficiently. Teaching and learning are evolving and developing in many countries, with a focus concerning what is actually learned through effective teaching methods. Design/methodology/approach A qualitative research was carried out, identifying effective teaching methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…The study, therefore, concludes that motivation, training, working environment, job stress, and students' behavior have a significant positive impact on the choice of teaching methods among academic staff of AL-Baha University in the country. This finding is consistent with earlier studies (e.g., Alam & Farid, 2011;Harter et al, 2015;Houtte, 2006;Reed & Brunson, 2018;Yakovleva & Yakovlev, 2014;Zenda, 2017) that have considered these factors as potential factors affecting teaching method in other countries.…”
Section: Research Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The study, therefore, concludes that motivation, training, working environment, job stress, and students' behavior have a significant positive impact on the choice of teaching methods among academic staff of AL-Baha University in the country. This finding is consistent with earlier studies (e.g., Alam & Farid, 2011;Harter et al, 2015;Houtte, 2006;Reed & Brunson, 2018;Yakovleva & Yakovlev, 2014;Zenda, 2017) that have considered these factors as potential factors affecting teaching method in other countries.…”
Section: Research Resultssupporting
confidence: 93%
“…Generally speaking, the choice of teaching methods based on the earlier stated factors is meant to culminate in the production of learners who are creative, proactive, problem-solvers, good decision-makers, critical thinkers, and good communicators (Nghiêm-Phú & Nguyễn, 2021;Zenda, 2017). What is more, Shirani Bidabadi, Nasr Isfahani, Rouhollahi, and Khalili (2016) observe that a good teaching method help students question their preconceptions as well as motivates them to learn, by putting them in a situation in which they see themselves as authors of answers and as agents of responsibility for change?…”
Section: Research Problemmentioning
confidence: 99%
“…Discussions, presentations, elaborations, and critique activities that formed key aspects of constructivist instruction enhanced understanding and memory of participants in the constructivist group (Andersen & Andersen, 2017;Connell et al, 2016;Hsu et al, 2019;Izzo, 2012;Kharb et al, 2013;Laal et al, 2013;McKnight et al, 2016;Montrieux et al, 2015;Öhrstedt & Lindfors, 2018;Zenda, 2017). The engagement phase provided learners with opportunity and much needed scaffolding which made them more focused and clearer on how to carry out investigations and what to discuss in the groups.…”
Section: Comparing Constructivist and Conventional Instructionmentioning
confidence: 99%
“…In addition to methods of hands-on activity simulation and games are methods that enhance students' understanding of Science subjects [8,9]. Collaborative and problem-solving activities also help students understand the content of Science subjects [10]. Other studies have found teamwork, responsibility, and collaborative learning appears to be the most important factors for effective learning [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%